Effect of In Vitro Gastrointestinal Digestion on the Polyphenol Bioaccessibility and Bioavailability of Processed Sorghum (Sorghum bicolor L. Moench) - Aduba Collins; Nidhish Francis; Kenneth Chinkwo; Abishek Bommannan Santhakumar; Christopher Blanchard (Molecules)
Sorghum is a significant source of polyphenols, whose content, antioxidant properties and bioaccessibility may be modulated by digestion. Studies have reported sorghum polyphenol changes after simulated digestion. However, the effects of simulated digestion on processed, pigmented sorghum are unknown. This study investigated the bioaccessibility and bioavailability of black (BlackSs and BlackSb), red (RedBa1, RedBu1, RedBa2, RedBu2) and white (WhiteLi2 and White Li2) sorghum samples using a Caco-2 in vitro model. Ultra high performance liquid chromatography—online 2,2′-azino-bis (3-ethylbenzothiazoline-6-sulfonic acid) (UHPLC–online ABTS)—and quadrupole time-of-flight liquid chromatography mass spectra (QTOF LC–MS) facilitated the identification of digested and transported compounds. Simulated digestion showed increased bioaccessibility and total phenolic content (TPC) for BlackSs by 2-fold. BlackSs and BlackSb exhibited high antioxidant capacities, with variations dependent on processing in other varieties. Kaempferol-3-O-xyloside exhibited a 4-fold increase in TPC following digestion of processed BlackSs and BlackSb but was absent in the others. BlackSs, BlackSb, and RedBu1 revealed twelve bioaccessible and Caco-2 transported compounds not previously reported in sorghum, including trans-pinostilbene, tryptophan and maackin a. This study demonstrates that in vitro digestion increases the bioaccessiblity of sorghum polyphenols through the process of cellular biotransformation, possibly improving transport and bioactivity in vivo.